Tanggung Jawab Notaris Akibat Adanya Pemalsuan Data Perjanjian Jual Beli Tanah Di Hadapan Notaris : (Studi Kasus Kantor Notaris Di Kota Mataram) - Khusnul Khotimah; Arief Rahman; Shinta Andriyani (Private Law, 2023)
The aims of this research are to know notary’s responsibility in data fraud in the making of land sale and purchase before notary by the parties, and also to know legal consequences of data fraud in notary office in Mataram City. Method of this work was empirical legal research which applied statute, conceptual and sociological approaches. The data was collected through library study and interview. Result of this work shows that notary does not responsible on the deed which made from fake data which brought to them by the parties. Legal consequences of the date which made based on fake data which brought by one party, it can be requested for revocation by the aggrieved party.